2018
DOI: 10.1002/adma.201704217
|View full text |Cite
|
Sign up to set email alerts
|

Stable Light‐Emitting Diodes Using Phase‐Pure Ruddlesden–Popper Layered Perovskites

Abstract: State-of-the-art light-emitting diodes (LEDs) are made from high-purity alloys of III-V semiconductors, but high fabrication cost has limited their widespread use for large area solid-state lighting. Here, efficient and stable LEDs processed from solution with tunable color enabled by using phase-pure 2D Ruddlesden-Popper (RP) halide perovskites with a formula (CH (CH ) NH ) (CH NH ) Pb I are reported. By using vertically oriented thin films that facilitate efficient charge injection and transport, efficient e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
236
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(238 citation statements)
references
References 67 publications
2
236
0
Order By: Relevance
“…Wang et al demonstrated 2D perovskite-based LEDs with high external quantum efficiencies of up to 11.7%, along with good stability [103]. Vertically oriented thin films of phase pure 2D perovskites were reported to have efficient charge injection and transport, and stable efficient EL with ultralow turn-on voltage ( Figure 5(e-g)) [104]. Furthermore, 2D halide perovskites were also employed to fabricate micro-ring laser arrays that showed high quality factor, high gain, and low threshold [105].…”
Section: And Quasi-2d Metal Halide Hybridsmentioning
confidence: 99%
“…Wang et al demonstrated 2D perovskite-based LEDs with high external quantum efficiencies of up to 11.7%, along with good stability [103]. Vertically oriented thin films of phase pure 2D perovskites were reported to have efficient charge injection and transport, and stable efficient EL with ultralow turn-on voltage ( Figure 5(e-g)) [104]. Furthermore, 2D halide perovskites were also employed to fabricate micro-ring laser arrays that showed high quality factor, high gain, and low threshold [105].…”
Section: And Quasi-2d Metal Halide Hybridsmentioning
confidence: 99%
“…Tsai et al synthesized 2D perovskite with the formula of (BA) 2 (MA) n −1 Pb n I 3 n +1 , and their results indicated that the stability of this LED was strongly correlated with the phase purity. [ 126 ] In addition, the pure 2D perovskite‐based LED showed highly stability after >14 h operation, which was much better than that of the 2D/3D hybrid or 3D perovskite‐based LEDs (degrade within minutes).…”
Section: Stability Of Perovskite Ledsmentioning
confidence: 99%
“…Quasi‐two‐dimensional (2D) Ruddlesden–Popper perovskites (RPP) are quantum‐well like materials, which have attracted considerable research interests recently for the application of light‐emitting diode (LED), solar cell, and photodetector . The chemical formula of RPP is L 2 A n −1 M n Y 3 n +1 , where L is the molecular ligand used as spacer cations such as butylammonium (BA) and phenethylammonium (PEA), A is methylammonium (MA) or formamidinium (FA), M is Pb or Sn, Y is halide anion, and n indicates the number of metal layers sandwiched between organic layers .…”
Section: Introductionmentioning
confidence: 99%